Performance Evaluation of EFB Biomass Supply Chain for Electricity Power Generation Based on Computer Simulation: Malaysia Case Study - Zahraee, S.M. (Springer, 2020)
Malaysia is one of the largest countries that has the largest palm oil plantation size in the world. Despite the enormous amount of palm biomass in the state, the use of biomass as fuel for power generation remains low. One of the most significant crises in energy supply from the biomass is to utilize it efficiently and effectively by considering lower cost of the supply chain and the process to change the biomass into useful energy source. In this paper, computer simulation is used to develop a model form current situation of empty fruit bunches (EFB) biomass Supply chain in Perak sate of Malaysia based on Arena software. The results found that, there are sixteen potential palm oil sites that had been analysed and met all the criteria of the case study according to their existing palm oil capacity, distance to the nearest power plant and minimum palm oil produced. The model had also been run with two different scenarios by decreasing the number of labour and increasing the number of trucks. First scenario showed that by decreasing the labors, output is decreased from 4.59 to 4.336Â ton/ha. In contrast, cycle time, value added (VA) time and other time are increased near 15, 25 and 15 respectively. Additionally, the final results based on the second scenario claimed that by assigning two truck, the output of the process is increased 23 (from 4.59 to 6.02Â ton/ha) compared to current situation as well as the time cycle of the whole process is increased from 7.2 to 8.95Â h because of an increase in VA and Other time (34 and 23). Â© 2020, Springer Nature Singapore Pte Ltd.